Enhancing the psychological well-being and sleep quality of healthcare providers with a multimodal psychological support program: a randomized controlled trial - Gao, Qi; Yao, Yuanyuan; Wang, Ruiyu; Zhang, Xinyue; Gudenkauf, Lisa M.; Xu, Guangxin; Harrison, Samantha; Zheng, Leilei; Wang, Jingping; Chen, Guanqing; Zheng, Bin; Ma, Haobo; et al. (Frontiers in Public Health, 2024)
BackgroundThe COVID-19 pandemic significantly challenged the global healthcare system, especially frontline healthcare professionals, such as those working in intensive care units (ICUs). In late 2022, a sudden increase in COVID-19 cases in China led to a large number of ICU admissions, requiring new ICU staff (non-ICU professionals to work in ICUs), exacerbating their stress. This study aimed to develop an effective stress management strategy for new ICU professionals, focusing on reducing the detrimental effects of stress on their psychological state. We hypothesized that the online multimodal psychological support (MPS) program might improve the psychological well-being and sleep quality of the participants.MethodsThis single-center, single-blind randomized controlled trial included new ICU staff during the COVID-19 pandemic. Participants were randomly assigned to either an intervention (online psychological support, MPS) or a control (routine wellness care, RWC) group for 28 days, and assessments were conducted before intervention (baseline), after intervention, and at the 1-month follow-up. The intervention included music therapy, sleep hygiene education, psychoeducation, and relaxation training, tailored to address common psychiatric issues experienced by healthcare professionals during the pandemic. The primary outcome was a DASS-21 score 28 days after the end of the intervention.ResultsOne hundred and one professionals eventually participated in the study, 47 in the MPS group and 54 in the RWC group. No significant differences were observed in the overall psychological well-being immediately after the end of the intervention. However, the MPS group showed improved sleep and sustained lower stress levels, anxiety, and depression scores at the 1-month follow-up, significantly improving the severity of insomnia (marginal mean difference −2.028; SE 1.00; p = 0.044).ConclusionThe online multimodal psychological support program effectively enhanced the psychological well-being and sleep quality of new ICU staff demonstrating the potential of off line training in managing stress and improving health outcomes during crises. The findings of this study emphasize the importance of accessible, flexible psychological support, especially in high-stress environments such as ICUs during pandemics.